Firm-Specific Variation and Openness in Emerging Markets - Li, Kan; Morck, Randall; Yang, Fan; Yeung, Bernard (The Review of Economics and Statistics, 2004)
This paper compares the comovement of individual stock returns across emerging markets. Campbell et al. and Morck et al. have shown that the United States saw rising firm-specific stock return variations, and thus declining comovement, over the second half of the twentieth century. We detect a similar, albeit weaker, pattern in most, but not all, emerging markets. We further find that higher firm-specific variation is associated with greater capital market openness, but not goods market openness. Moreover, this relationship is magnified by institutional integrity (good government). Goods market openness is associated with higher marketwide variation.